ChemInform Abstract: An Efficient Domino Knoevenagel/Hetero‐Diels—Alder Route to Some Novel Thiochromenoquinoline‐Fused Polyheterocycles. Issue 48 (2nd December 2014) - Parmar, Narsidas J.; Labana, Balvantsingh M.; Barad, Hitesh A.; Kant, Rajni; Gupta, Vivek K.
Abstract under solvent‐free reaction conditions